2022
DOI: 10.1007/s10072-022-05901-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of quarantine applied during the COVID-19 pandemic on mental health and quality of life in patients with multiple sclerosis and healthy controls

Abstract: Background The coronavirus outbreak, which emerged in Wuhan, China, in late 2019 and spread to the world, has changed each of our lives. Objective To investigate the effects of quarantine on depression, anxiety, sleep quality, fatigue, and SF-36 of multiple sclerosis (MS) patients during the COVID-19 outbreak and differences between healthy controls (HC). Methods Eighty-six MS patients and 65 HC patients were included in the study. Participants filled out the various scales through face-to-face interviews for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Evidence shows that during COVID-19 pandemic, patients with MS experienced higher fatigue and weaker mental health indicators. In addition, they left their home less frequently and had less daily activities [ 46 , 47 ]. Probably, for these reasons, the participants of this study used the services provided in the MS Association less than before.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that during COVID-19 pandemic, patients with MS experienced higher fatigue and weaker mental health indicators. In addition, they left their home less frequently and had less daily activities [ 46 , 47 ]. Probably, for these reasons, the participants of this study used the services provided in the MS Association less than before.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 pandemic affected especially people with neurological health conditions not only due to the infection but also because of the general lockdown followed by social distancing [6] . Studies suggest that restrictions during the COVID-19 pandemic could potentially affect the quality of life in patients with multiple sclerosis (MS) [7] and Parkinson’s disease (PD) [8] mainly due to the lack of social interaction. A recent systematic review concluded that 60% of studies reported changes in cognition and 93% of studies reported worsening psychological symptoms in patients with dementia [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Another potential source of vulnerability that could compromise the ability of people with MS to manage pandemic-related challenges is their high rate of underlying emotional abnormalities [ 6 ]. A number of studies have addressed this concern.…”
Section: Introductionmentioning
confidence: 99%